Paramètres biochimiques sériques des lapins (Oryctolagus cuniculus linnaeus, 1758) nourris avec des aliments à base de ressources alimentaires d’Afrique de l’Ouest : Synthèse bibliographique - ATCHADE, Ghislaine Sègbédji Théodora; ATCHADE, Ghislaine Sègbédji Théodora; MENSAH, Serge Egide Paulin; HOUNDONOUGBO, M. FRÉDÉRIC; Attakpa, Sèlidji Eugène (My University, 2019)
Biochemistry parameters evaluation is a reliable technique used to assess and monitor animal’s health and nutritional status. Objective: The present review paper focused on studies related to the assessment of serum biochemical parameters in rabbits in West Africa. Methodology and Results: In order to realize this literature review on the biochemical profile of rabbits in West Africa, many scientific papers were consulted and analyzed. Information collected shows that rabbit’s serum biochemical parameters are notably evaluated during studies on the valorization of a local feedstuffs available in West Africa. These scientific papers indicate that 11 serum biochemistry parameters are mainly evaluated in rabbits bred in Africa. These are Albumin, Globulin, Glucose, Cholesterol, Urea, Total Protein, Creatinine, ASAT, ALAT, Uric Acid and Triglycerides. Conclusion and application of results: Levels of each serum biochemistry parameters recorded by the different authors in rabbits in West Africa show that they vary enormously according to the feedstuffs used to feed them. The large variation obtained in levels of each biochemical parameters evaluated in different studies conducted in Africa, shows that rabbit’s biochemical profile varies enormously according to the local feedstuffs used in their feeding them. This confirms that feeding leads to significant variations in biochemical parameters. The different biochemical profiles of rabbits listed in the scientific papers consulted will allow a comparison with the biochemical profile of rabbits fed with concentrated feedstuffs in characterisation in Benin.
Keywords: Local Feedstuffs; Serum Biochemistry Parameters; Rabbit; West Africa